2023
DOI: 10.3390/polym15051175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Denture Disinfectants on the Mechanical Performance of 3D-Printed Denture Base Materials

Abstract: Denture care and maintenance are necessary for both denture longevity and underlying tissue health. However, the effects of disinfectants on the strength of 3D-printed denture base resins are unclear. Herein, distilled water (DW), effervescent tablet, and sodium hypochlorite (NaOCl) immersion solutions were used to investigate the flexural properties and hardness of two 3D-printed resins (NextDent and FormLabs) compared with a heat-polymerized resin. The flexural strength and elastic modulus were investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“… 38 , 39 Previous studies showed that 3D printed-denture base resins have lower hardness compared to PMMA-based resins. 40 , 41 Alkaltham, et al 41 (2023) found that immersion in alkaline peroxide and sodium hypochlorite 1% for 180 days decreased the Vickers hardness of 3D-printed resins and did not change the hardness of PMMA. Thus, we hypothesize that the lower hardness of the 3D-printed resins, as well as the hardness reduction when these materials are immersed in disinfectant solutions, increases the susceptibility to the adhesion of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 Previous studies showed that 3D printed-denture base resins have lower hardness compared to PMMA-based resins. 40 , 41 Alkaltham, et al 41 (2023) found that immersion in alkaline peroxide and sodium hypochlorite 1% for 180 days decreased the Vickers hardness of 3D-printed resins and did not change the hardness of PMMA. Thus, we hypothesize that the lower hardness of the 3D-printed resins, as well as the hardness reduction when these materials are immersed in disinfectant solutions, increases the susceptibility to the adhesion of microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that when selecting a cleaning solution, it is important to consider which cleaning solution will result in the best long-term retention when used with a specific attachment system. For removable dental prostheses wearers, different denture cleansers and cleaning methods were recommended to prevent microbial adhesion and subsequently prevent denture stomatitis occurrences [ 19 , 27 ]. Effervescent denture cleansers (Corega and Fittydent) are most commonly used due to their efficacy in decreasing C. albicans adhesion in addition to its ability in removing light stains and debris loosing from denture surfaces [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…11,19 Biofilm that develops on denture surfaces is to be removed as part of denture care to prevent oral infections. 10 Several CDCs have been investigated for their antimicrobial characteristics in the past. Among these are the readily available and easyto-use alkaline peroxides (Corega), H 2 O 2 , and mouth rinses (CHX).…”
Section: Discussionmentioning
confidence: 99%
“…5 In such cases, chemical denture cleansers (CDCs) are recommended instead of mechanical cleansing. [8][9][10][11] In addition, CDCs alone or in combination with mechanical brushing can be used by denture wearers to prevent microbial infections that frequently cause denture stomatitis. 11 CDCs may come in liquid, powder, or tablet form, [5][6][7] and can be classified according to their constituents and mechanism of action into hypochlorite, peroxides, enzymes, weak acids, and mouth rinses.…”
mentioning
confidence: 99%